ACODE Learning Modalities 2022. - Selvaratnam, Ratna (Australasian Council on Open Distance and eLearning (ACODE), 2022)
Based on a May 2022 survey of Australasian Council on Open Distance and eLearning (ACODE) members, this report shows changes in the mode teaching and learning is delivered at higher education institutions in Australasia, with significant disruption to in-person delivery. It compares delivery of lecture, laboratory, workshop, seminar, ensemble, studio, tutorial, practicum, intensives and work integrated learning and considers reasons such as evolving pedagogies, access and inclusion, student feedback, technology advances and the pandemic. [Publisher summary, ed]